Switching from Worldwide to Territorial Taxation: Empirical Evidence of FDI Effects - Thiess Büttner; Carolin Holzmann (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper explores empirically whether and how FDI is affected if multinationals' home countries change taxation of foreign earnings by switching from worldwide to territorial taxation. Our analysis employs data for German inbound FDI based on the ultimate investing country concept. We use a quasi-experimental approach and provide counterfactuals using the synthetic-control method. Our results confirm effects of the switch from worldwide to territorial taxation on FDI but point at the importance of the actual tax rate. For Japan, which charges a higher tax rate on corporate profits than Germany, we find a substantial increase of FDI in Germany after the switch from worldwide to territorial taxation. For the UK, which imposes a lower tax rate than Germany, the switch to territorial taxation is not found to exert any significant effects on investment in Germany.
Keywords: H25; F23; 330; FDI; double taxation; dividend exemption; tax competition; synthetic-control method; ultimate investor country